Progress in application of structured education program for stroke patients (结构化教育在脑卒中患者的应用进展) - ZHANG Xiuli (张礼秀); CHEN Hong (陈红); CEN Mei (岑梅) (Journal of International Translational Medicine Limited, 2022)
Structured educational program refers to the systematic educational program which follows the standard and evidence. A structured educational program contains a list of disease self-management measures, and designed to improve the self-management skills of patients. This paper reviewed the studies about structured education program from aspects of its concept, standard, methodology, forms, application status and effectiveness, in order to prove reference ofr the health education and management of stroke patients. (结构化教育是一种标准化、系统化的健康教育形式, 有循证依据, 包含疾病所有重要自我管理内容, 在提高患者自我管理能力方面有良好效果。本文对结构化教育的概念、标准、方法和形式、脑卒中结构化教育的现状与应用效果等方面进行综述, 旨在为脑卒中患者的健康教育和管理提供参考。)